Factors Affecting Visit Decision Through Visitor Satisfaction at M Bloc Space Jakarta - Amrullah, Amrullah; Oktovia, Reno Catelya Dira; Oktovianus, Oktovianus; Hamzah, Hanafi (Journal of Business on Hospitality and Tourism, 2023)
This research aims to determine the influence of tourist facilities and attractions on visiting decisions through tourist satisfaction at M Bloc Space Jakarta. The research method used is path analysis with a quantitative descriptive research type. The population is all visitors who visited M Bloc Space Jakarta from June to August 2023. The sample taken was 100 visitors who were determined based on the Slovin formula. Sampling was carried out using the Accidental Sampling technique. Partial research results show: (1) Tourist facilities and tourist attractions have a significant influence on visitor satisfaction; (2) tourist facilities, tourist attractions, and visitor satisfaction together have a significant influence on the decision to visit; (3) Tourist facilities and tourist attractions also have a significant influence on visiting decisions through visitor satisfaction. Good tourist facilities and attractions not only directly influence visitor satisfaction, but also have an impact on their decision to return to visit M Bloc Space Jakarta. M Bloc Space managers are expected to (1) establish partnerships with the local creative community and collaborate with local artists, startup companies and music groups to increase the attractiveness of M Bloc Space as a center for creativity, while providing added value for visitors. (2) In addition, they are expected to create interactive experiences at M Bloc Space through exploratory art installations, interesting selfie areas, and creative stations that allow visitors to create their own works. This experience encourages visitors to share with others, strengthening M Bloc Space's appeal as a unique and interesting destination.